Principal Management - Nurlinda Nurlinda (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
This study aims to determine the Principal Management in the Implementation of Local Culture-Based Education in Madrasah Aliyah Negeri Malili, East Luwu Regency. The research method used is descriptive qualitative using a pedagogic approach that uses several educational theories to examine educational problems and a management approach that includes planning, organizing, implementing, and monitoring. Data collection techniques used are observation, interviews, and documentation. The research instrument is the researcher as the vital instrument. Complementary to this research instrument are observation sheets, interview guides, stationery, and cameras. Data were analyzed using three steps, namely data reduction, data presentation, and concluding. The results showed that the principal's management in implementing local culture-based education was carried out by implementing planning, organizing, implementing, and supervising. The principal tries to organize all activities, directs various activities, regulates school relations with outside parties, has the right to make school decisions, and carries out educational supervision. By applying the local culture at Madrasah Aliyah Negeri Malili, namely lempu‟, acca, sitinaja, getteng, reso‟, and siri‟. The inhibiting factors are increasingly sophisticated and modern technological advances, lack of communication, and lack of socialization about local culture-based education. While the supporting factors are the exemplary principals and teachers fostering through an approach by habituation to come to school on time, teachers shake hands with each other, greet each other, greet each other with a smile, and say hello.